Community Participation in Social forestry in Tamil Nadu : some Critical Issues - Rajendran, S. (Indian Forester, 1994)
In the recent past policy makers and planners started advocating community participation for the effective implementation of development and welfare programs. As it was realized that people’s participation bears positive impact on Social Forestry Program, the implementing authorities emphasized the greater role of community participation. Nevertheless, some lacunae on people’s participation in SFP have been witnessed in many parts of the country. As such, this paper attempts to highlight the problems and prospects of community participation in SFP based on an extensive survey conducted in two districts of Tamil Nadu.